Tekanan Cuff Endotracheal Tube (ETT) Pada Pasien Terintubasi Di Intensive Care Unit - Setiyawan Setiyawan; S Dwi Sulisetyawati (Interest : Jurnal Ilmu Kesehatan, 2018)
Backgound: Inaccuracy granting ETT cuff pressure can cause a risk of complications that increase the risk of aspiration and trauma to the trachea. Cuff management includes cuff development techniques and intracuff pressure monitoring is a critical component in the treatment of ETT intubated patients in intensive care. The aim of this study was to find out the description of ETT treatment especially on intracuff pressure monitoring. Method: The research methods is a descriptive study in 30 intubated patients in the intensive room of Bagas Waras Klaten Hospital. Result: Based on observations 4 (four) hours after ETT cuff development using cuff inflator, the average results of initial ETT cuff pressure measurements were 28 cmH2O ± 17.43, then after four hours 19.63 cmH2O ± 17.43. In conclusion, ETT cuff development using a cuff inflator will tend to decrease intracuff pressure. Conclusion: Periodic monitoring of intracuff pressure is needed to achieve optimal pressure so there are no complications caused by underinflation or overinflation.